Nuclear dimension and Z-stability - Sato, Y; White, S; Winter, W (Springer Verlag, 2015)
Simple, separable, unital, monotracial and nuclear C$^*$-algebras are shown to have finite nuclear dimension whenever they absorb the Jiang-Su algebra $\mathcal{Z}$ tensorially. This completes the proof of the Toms-Winter conjecture in the unique trace case.